The influence of a business ethics course on ethical judgments of Malaysian accountants - Mohd Ghazali, Nazli Anum (Emerald, 2015)
The purpose of this paper is to examine the influence of ethics instruction received during tertiary education on ethical judgments of Malaysian accountants. data were obtained through questionnaire survey and analyzed using regression analysis. A total of 221 respondents representing a 88.4 per cent response rate completed the questionnaire. The regression results show that ethics instruction received during tertiary education have a significant impact on both legal and illegal business scenarios. Accountants also judged an illegal questionable scenario stricter than a legal questionable scenario. The questionnaires were distributed to those firms which participated in the internship programme. Although firms which participated were of varying sizes, care still needs to be taken in interpreting the results, as representativeness remains an issue in studies of small size. The findings appear to suggest that ethics is an important factor influencing ethical judgments. Hence, the subject should be taught at least at the tertiary level so as to inculcate ethical values early in younger generation. An ethically imbued workforce can be expected to make sound and equitable corporate decisions. The study offers preliminary insight into the benefit of introducing the business ethics course in the undergraduate accounting programme at public universities in Malaysia.